Ruang Lingkup Rekayasa Sipil 2020 di Indonesia - Besari, Mohammad Sahari (Center for Research and Community Services ITB, 1996)
At the end of the Second Long -Term Development Plan (2020), the percentage of urban population in Indonesia will be greater than rural population. This phenomenon will put tremendous pressure on the provision of physical infrastructure to the population. Physical infrastructure is strongly related to Civil Engineering. Entering the 21st century and beyond, the development of civil engineering will be greatly influence by Material Science and Computer Science.The increase of infrastrucure development in the next 25 years will also increase the need for Civil Engineering Human Resources. The quality and quantity of Civil Engineers in Indonesia are still relatively low. To anticipate the need of infrastructure development in The Second Long-Term Development Plan, the quality and the output of Civil Engineering graduates need to be increased.